2008
DOI: 10.1590/s1415-790x2008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em pessoas com lesão medular traumática: um estudo com o WHOQOL-bref

Abstract: Esse estudo integra a pesquisa "Qualidade de Vida nos Portadores de Lesão Medular: paraplégicos que se autocuidam", realizada junto ao Programa de Pós-Graduação em Ciências da Saúde da Universidade de Brasília. As fontes de financiamento para a pesquisa são próprias dos pesquisadores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
22
1
38

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 18 publications
(15 reference statements)
9
22
1
38
Order By: Relevance
“…This comprises facets, (including: safety, educati on, leisure, housing, health service access and transportati on), whose sati sfacti on depends on fi nancial capacity. This result is not only related with SPI pati ents' assessment of their own economic capacity as not at allvery poor (80.9%), but also support the results of a study at Hospital Sarah in Brasília (18) , in which the WHOQOLbref was used for QoL assessment, in which the worst assessment scores were related with the environment and health.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This comprises facets, (including: safety, educati on, leisure, housing, health service access and transportati on), whose sati sfacti on depends on fi nancial capacity. This result is not only related with SPI pati ents' assessment of their own economic capacity as not at allvery poor (80.9%), but also support the results of a study at Hospital Sarah in Brasília (18) , in which the WHOQOLbref was used for QoL assessment, in which the worst assessment scores were related with the environment and health.…”
Section: Discussionsupporting
confidence: 84%
“…This result confi rms a research report with a sample of mostly young and single men, who had fi nished primary educati on and scored psychological health and social relati ons bett er (18) ; but diff ers from the results of a study in Fortaleza (13) and another developed in Australia and Sweden (19) . In those studies, the authors reported that social aspects received the lowest average score, due to SCI pati ents' dissati sfacti on because they considered themselves at a social disadvantage.…”
Section: Discussionsupporting
confidence: 48%
“…According to Bampi and coworkers 15 , who studied patients with spinal cord injury in a Rehabilitation Hospital in Brasilia, utilizing the WHO assessment instrument for quality of life, WHOQOL, the domains linked to the environment and to physical health had the worse evaluation scores. In this case, physical health was related to complications as a result of spinal cord injury 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo foi observada maior prevalência de fraturas da coluna vertebral nos indivíduos do sexo masculino (82%) com média de idade de 38±17 anos, o que é concordante com outros estudos nacionais [7][8][9] , e é habitualmente explicado pelo fato de os homens jovens se exporem mais às atividades de risco e possuírem comportamento mais desafiador.…”
Section: Discussionunclassified